2016
DOI: 10.1002/ejlt.201500597
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cholesterol oxides in lipid medium during microwave heating

Abstract: Microwave (MW) heating of foods may cause the formation of cholesterol oxidation products (COPs). COPs formation depends on the conditions of MW heating and the composition of the food matrix. The aim of this work was to study the formation of major COPs from cholesterol incorporated into palm, extra virgin olive, soybean, or fish oils during MW heating, and to monitor changes in peroxide value and fatty acid (FA) profiles. Model systems composed of mixtures of cholesterol and oil (2.5 mg of cholesterol/g oil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The air fryer caused an increase of the total saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) contents in the thermal processed samples, between 11.8% and 20.6 %, respectively. Similar results were reported by Leal‐Castañeda and others () in fish oil after microwave heating; Gladyshev and others () in boiled and roasted humpback salmon; and Garcı́a‐Arias and others () in boiled and grilled sardines.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The air fryer caused an increase of the total saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) contents in the thermal processed samples, between 11.8% and 20.6 %, respectively. Similar results were reported by Leal‐Castañeda and others () in fish oil after microwave heating; Gladyshev and others () in boiled and roasted humpback salmon; and Garcı́a‐Arias and others () in boiled and grilled sardines.…”
Section: Resultssupporting
confidence: 88%
“…The temperature used and the time required to prepare fish and fish products are perhaps the main factors that contribute to the degradation of cholesterol, forming cholesterol oxidation products (COPs) (Dantas and others ; Leal‐Castañeda and others ). These substances are structurally similar to cholesterol and are normally present in small quantities formed by endogenous metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this level rose and was recorded to be significantly higher in fried meat samples, suggesting that these COPs require higher temperatures and longer cooking times to be produced. Other studies have demonstrated that 7-keto abundantly forms during microwave heating as compared to frying [14]. Interestingly, a long heating time (>12 min) significantly elevated triol and 7-keto COPs [49,50].…”
Section: Discussionmentioning
confidence: 86%
“…The degradation of cholesterol due to oxidation produces COPs. Small COP quantities are present in foods due to endogenous metabolic processes [13,14]. However, exogenous COPs can also be produced in foods due to many factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…During thermal processing, changes such as a loss of antioxidant enzyme activity, disruption of cell membranes, which bring polyunsaturated fatty acids into contact with pro-oxidants, and thermal decomposition of hydroperoxides to pro-oxidant species are responsible for the increase in cholesterol oxidation rate (Hur et al, 2007). Many authors have investigated the instability of the cholesterol molecule during thermal processing (Ansorena et al, 2013;Barriuso et al, 2016;Derewiaka, & Molińska, 2015;Ferreira et al, 2017;Freitas, Amaral, Coutrim, Afonso, & Junqueira, 2015;Leal-Castañeda, Hernández-Becerra, Rodríguez-Estrada, & García, 2017;Saldanha, Benassi, & Bragagnolo, 2008;Tarvainen, Quirin, Kallio, & Yang, 2016;Xu et al, 2016).…”
Section: Cholesterol Oxidationmentioning
confidence: 99%